PENGEMBANGAN PERANGKAT PEMBELAJARAN MENGGUNAKAN MODEL PEMBELAJARAN GUIDE INQUIRY BERBASIS âQAITâ PADA MATA KULIAH STRUKTUR ALJABAR I MATERI GRUPOIDA - Lusiana, Restu; Andari, Tri (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2014)
The aims of this research is to create a good learning tools of Algebra Stucture towards âQAITâbased Guide Inquiry. Algebra Stucture as basic subject in mathematics. This conditions is essensials for students to comprehend the materials. The using of âQAITâ based Learning Model Guide Inquiry is one of the ways to incrase motivation student on learning. âQAITâ based Learning Model Guide Inquiry will increase the active learning of the students. This developmental research was applying Thiagarajanâs,et al. 4D developmental approach. Thiagarajanâs approach consisted of 4D phases approaches. The phases are Define, Design, Development and Disseminate. The population was students of fifth semester of Mathematics Department of IKIP PGRI Madiun. The data collections techniques used were in form of test and non-test (questionnaire). The results were collected from the approachâs trial. Learning tools already stated valid and has good criteria on studentsâ effective activities, lecturerâs classroom management, sensitiveness of studentsâ results test, validity, reliability, and studentsâ positive responses. Good learning tools of Algebra Stucture towards âQAITâbased Guide Inquiry creates (1) Satuan Acara Pembelajaran (SAP), (2) Lembar Kegiatan Mahasiswa (LKM), (3) Tes Hasil Belajar (THB) of Spatial-n Euclides of Linear Algebra.Keywords: Development, Learning Tools, âQAITâ Based Guide Inquiry, Grupoida